2016
DOI: 10.1111/apm.12519
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of clear cell renal cell carcinoma identifies CSNK2A1, SPP1 and DEFB1 as promising novel prognostic markers

Abstract: The prognosis associated with clear cell renal carcinoma (ccRCC) can vary widely and novel molecular prognostic markers are needed to assess prognosis at an earlier stage. Several gene products have been investigated for this purpose, but none of them have been implemented in clinical practice. Here we hypothesized that we, using TaqMan® Array, could identify superior prognostic messenger RNA (mRNA)s in long-term follow-up. Messenger RNA level of 19 candidate genes was investigated in 97 patients with ccRCC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 55 publications
(65 reference statements)
1
41
3
Order By: Relevance
“…DEFB1 encodes b-defensin, which belongs to a family of antimicrobial peptides produced by white blood cells and epithelial cells. Rabjerg and colleagues (40) suggested that DEFB1 might be a tumor suppressor gene, but our results revealed that high expression of this gene predicted a worse prognosis with very weak significance (P ¼ 4.99eÀ2; HR ¼ 1.41, and 95% confidence interval ¼ 1.00-1.98). EDNRB is a member of the endothelin axis, and TSPAN7 is a member of the transmembrane 4 superfamily.…”
Section: Lasso-cox Risk Index Is Independent Of Known Prognostic Factorscontrasting
confidence: 67%
See 1 more Smart Citation
“…DEFB1 encodes b-defensin, which belongs to a family of antimicrobial peptides produced by white blood cells and epithelial cells. Rabjerg and colleagues (40) suggested that DEFB1 might be a tumor suppressor gene, but our results revealed that high expression of this gene predicted a worse prognosis with very weak significance (P ¼ 4.99eÀ2; HR ¼ 1.41, and 95% confidence interval ¼ 1.00-1.98). EDNRB is a member of the endothelin axis, and TSPAN7 is a member of the transmembrane 4 superfamily.…”
Section: Lasso-cox Risk Index Is Independent Of Known Prognostic Factorscontrasting
confidence: 67%
“…Using univariate and multivariate Cox proportional hazards analysis, we performed a comprehensive comparison between the lasso-Cox risk index and other known prognostic biomarkers, including two clinical variables, grade (G1þG2 vs. G3þG4), stage (IþII vs. IIIþIV), six gene expression signatures (39,40), CSNK2A1, SPP1, DEFB1, PECAM1, EDNRB, TSPAN7, and five somatic mutation genes (26,(41)(42)(43)(44)(45)(46), VHL, PBRM1, BAP1, SETD2, TP53. Patient subtyping for gene expression signatures was carried out by using the median as cut-off point.…”
Section: Lasso-cox Risk Index Is Independent Of Known Prognostic Factorsmentioning
confidence: 99%
“…For example, in Bae JS's study, CSNK2A1 was found to participate in the progression of breast carcinoma and to indicate poorer patient survival ( 77 ). In addition, Rabjerg et al ( 78 ) identified CSNK2A1 as a promising novel prognostic biomarker in clear cell renal carcinoma. Furthermore, CSNK2A1 has also been found to be involved in ovarian cancer ( 79 ), oral cancer ( 80 ), prostate cancer ( 81 , 82 ) and pancreatic cancer ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study based on gastric cancer cell lines indicated that the elevated expression of SPP1 is a critical determinant of poor prognosis and that OPN expression could help to predict the risk of hematogenous metastasis [28]. In addition, in a recent study, SPP1 was observed to be a novel prognostic marker for clear cell renal cell carcinoma [29]. Previous research concerning esophageal squamous cell carcinoma has also suggested that the elevated expression of SPP1 in tumor tissues was associated with poor prognosis [30].…”
Section: Zhuo Et Al: Tissue-specific Biomarkers For Gc Prognosismentioning
confidence: 99%